Of Materialism and Anomie: A Revisiting of the Yoruba People's Omoluabi Ethos - Oladejo, Abiodun Omotayo; Dastile, Nontyatyambo Pearl (African historical review, 2025)
This article explores Euro-American materialist ideologies and analyses their percolation in Africa. We argue that precontact Africa had a unique socio-economic environment which was based on established traditions and an established worldview. We posit that the incursion of Western materialist values into Africa produced a dialectical crisis-with external values, backed by colonial forces, displacing the indigenous, African conceptions about material existence. This displacement underlies the plethora of social problems being witnessed in Africa today. The article thus foregrounds the need for Africa to look inwards for remedial measures that can counteract the effects of Euro-American material ideologies and, possibly, put the continent on the path of cultural recovery. We argue that the Omoluabi ethos of the Yoruba people-a major ethnic group in Nigeria, which, inter alia, spreads to other West African countries and the Caribbean-provides the philosophical underpinning capable of engendering the moral and cultural revival that the continent requires to resolve most of the elements of the social disorganisation that the Euro-American material conception of life has brought on Africa. The Yoruba principle of Omoluabi valorises such attributes as community, sound character, diligence, loyalty, and kindness. If embodied by Africans-and other colonised peoples-this principle will, among other things, produce such outcomes as equitable economic distribution, improved well-being, reduction in crimes, and environmental protection. The article proposes a framework to upscale the Omoluabi ethos in Africa that involves collective recollection, value recommitment, and resilience.